Adversity Quotient in the Implementation of Project-Based Learning - Dina Mardiana; Sofa Amalia (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2022)
The merdeka curriculum establishes project-based learning as a learning design for developing soft skills and student character to support the development of the Pancasila Student Profile character. As a new paradigm, students must be responsive in following the existing learning schemes in the merdekacurriculum structure. Therefore, a good Adversity Quotient is needed for students as a benchmark for psychological adaptability in facing learning obstacles and fulfilling learning outcomes according to the objectives of the merdeka curriculum. Therefore, this research focuses on the efforts of SMK Negeri 4 Malang to develop students' Adversity Quotient through project-based PAI learning. Through a qualitative approach and type of case study research, this research assembles a critical analysis that can unravel the root of the problem as well as efforts to develop an Adversity Quotient for students at SMKN 4 Malang so that it has implications for achieving learning objectives according to the mandate of the merdekacurriculum. Data was collected through interviews, participant observation, and documentation studies. Data analysis was performed using the interactive model Miles, Huberman and Saldana. This study concludes that students' Adversity Quotient can develop through four stages called DEAL (Listen, Explore, Analyze, Do). The four stages are empirically able to frame the axiological framework for developing Adversity Quotient in students during the project-based learning (PjBL) process at SMKN 4 Malang.